Accountancy mathematics for UiTM - Lau, Too Kya (Oxford Fajar Sdn.Bhd, 2009)
This book is written for first year students in Universiti Teknologi MARA who are pursuing Diploma in Accauntancy as well as for students from other institutes of higher learning who are pursuing professional courses like finance, business studies, business administration and commerce. Business practitioners may also find this book is useful.